2009
DOI: 10.1126/science.1175194
|View full text |Cite
|
Sign up to set email alerts
|

A Vital Role for Interleukin-21 in the Control of a Chronic Viral Infection

Abstract: Controlling Chronic Viral Infections Chronic viral infections such as HIV and hepatitis B and C viruses are major public health concerns. T cell—mediated immune responses are critical for controlling viral infections. In contrast to acute infections, chronic viral infections are characterized by “exhausted” cytotoxic CD8 + T cells, cells which exhibit reduced proliferative capacity, cytokine secretion, and cytotoxicity. Treatments that reverse exhaustion result in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
466
2
2

Year Published

2010
2010
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 447 publications
(493 citation statements)
references
References 30 publications
23
466
2
2
Order By: Relevance
“…One possibility is that soluble factors produced by activated CD4 T cells act directly on exhausted CD8 T cells. Recent studies have shown that IL-21 produced by CD4 T cells plays a critical role in maintaining CD8 T-cell function during chronic LCMV infection (36)(37)(38). IL-21 has also been shown to enhance HIV-specific CD8 T cell function in vitro (39).…”
Section: Discussionmentioning
confidence: 99%
“…One possibility is that soluble factors produced by activated CD4 T cells act directly on exhausted CD8 T cells. Recent studies have shown that IL-21 produced by CD4 T cells plays a critical role in maintaining CD8 T-cell function during chronic LCMV infection (36)(37)(38). IL-21 has also been shown to enhance HIV-specific CD8 T cell function in vitro (39).…”
Section: Discussionmentioning
confidence: 99%
“…Cependant, les éléments régulateurs clés produits par les cellules T CD4 + et nécessaires à l'obtention d'une réponse antivirale complète et efficace étaient jusqu'à récemment, mal compris, voire inconnus. Trois études récentes réalisées sur des mo dèles in vivo murins d'infection virale persistante par le lymphocytic choriomeningitis virus (LCMV) ont démontré le rôle clé de l'IL-21 dans la réponse antivirale [14][15][16]. Lors de ces études, les auteurs ont utilisé deux souches différentes de LCMV (clone 13 et Armstrong) qui possèdent une pathogénicité différente chez l'animal inoculé.…”
Section: L'interleukine-21unclassified
“…L'injection directe d'IL-21 à des souris ne possédant pas de cellules T CD4 + a permis de restaurer les fonctions antivirales exprimées par les cellules T CD8 + ainsi que de réduire la charge virale chez ces souris [16]. L'IL-21 ne semble donc pas être nécessaire à la génération des cellules T CD8 + spécifiques du virus, mais elle serait importante pour la qualité de la réponse antivirale [16]. Ces études suggèrent le rôle indispensable de l'IL-21 au stade chronique de l'infection, plutôt qu'au stade de l'infection aiguë.…”
Section: Revuesunclassified
“…IL-21 secreted by activated CD4 1 T cells was essential for the maintenance of specific CD8 1 T-cell functions and control of viremia in lymphocytic choriomeningitis virus infection. [6][7][8] CD4 1 T cells from individuals with sustained immune control of HIV-1 infection produced larger amounts of IL-21 upon stimulation with phorbol myristate acetate/ionomycin or HIV-1 gag peptides. Of note, exogenous IL-21 significantly increased HIV-1-specific CD8 1 T-cell effector functions.…”
Section: Function Of Il-21 In Cellular Immune Responsesmentioning
confidence: 99%
“…In mouse models of chronic lymphocytic choriomeningitis virus infection, IL-21 produced by virus-specific CD4 1 T cells was essential for sustaining antiviral functions of CD8 1 T cells and preventing them from immune exhaustion. [6][7][8] Acutely-resolved hepatitis C virus was characterized by strong Th1/Th17 responses with specific expansion of IL-21-producing CD4 1 T cells and increased IL-21 levels in the plasma. 9 In patients with HIV-1 infection, reduced IL-21 production could be a contributing factor to the compromised cellular and humoral immune responses.…”
Section: Introductionmentioning
confidence: 99%